BLOOD GLUCOSE TARGET ACHIEVEMENT AND ANTIDIABETES REGIMEN IN TYPE-2 DIABETIC GERIATRIC PATIENTS - Budi Suprapti (Indonesian Journal of Pharmacy, 2014)
Diabetes mellitus (DM) is a leading caused morbidity in geriatric patients. The prevalence of type-2 DM is more than 90% of DM population and increase with age, and half of those patients were geriatric. Blood glucose (BG) control is important for prevention diabetes complications, but attention must be given in geriatric patients due to the increasing susceptibility to risk of hypoglycemia. The aimed of this study was to identify BG achievement in diabetic geriatric patients and its therapeutic management. This study was done in Outpatient Geriatric Clinic, Dr. Soetomo General Hospital Surabaya Indonesia in the period of March to June, 2012. The inclusion criteria were type-2 diabetic geriatric patients with/without diabetic complication that received antidiabetic therapy and had BG data. The results from 165 patients showed that BG target achieved by 53% patients, 41% patients not achieved the target, while 6% patients in risk ofhypoglycemia. Management therapy for patients with achieved BG target was done by (1) continued therapy as before, (2) increasing dosage regimen for patients with BG already in the target but still within the upper limit target or decrease dosage regimen for patients with BG in lower limit target to avoid hypoglycemia, (3) change type of medication for patients who experienced side effects. Meanwhile, from all patients that failed to achieve BG target there were some patients received additional medications and regimen changes, but the rest of those didn’t receive any additional medication or regimen changes, which were many of them eventually became one of the drug-related problems in this patient group. In conclusion, there were still quite large number patients that did not achieve BG target, therapy management changes were made based on BG profile and there were drug related problems related to dosage regimen that needs pharmaceutical care intervention